Faktor-Faktor yang Berhubungan dengan Status Gizi Anak Balita di Wilayah Kerja Puskesmas Sikumana - Maria Kristina Bebhe; Anna Henny Talahatu; Daniela L. A Boeky (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Nutritional status is a picture of the balance of nutrient intake that enters the body with what the body needs. Toddlers are an important age group in the growth and development of children physically and mentally. This study aimed to analyze the factors associated with the nutritional status of toddlers in the Sikumana Health Center working area. This study used a cross-sectional study approach. The sample consisted of 94 toddlers with a simple random sampling technique. Research data collection using questionnaires. The data obtained were analyzed using the Rank Spearman correlation test with a significance level of α = 0.05. The results of the study according to the WHZ, indicate that there is a significant relationship between energy intake (p=0.000) protein intake (p=0.000) household food expenditure (p=0.001) maternal nutritional knowledge (p=0.003) maternal education (p=0.019) maternal employment (p=0.003) exclusive breastfeeding history (p = 0.036) history of infectious diseases (p = 0.000). The results of the study according to the WAZ, shows that there is a relationship between energy intake (p=0.000) protein intake (p=0.001) household food expenditure (p=0.002) maternal nutritional knowledge (p=0.001) the history of exclusive breastfeeding (p=0.019) and the history of infectious diseases (p=0.002). In this study, maternal education (p=0.909) and maternal employment (p=0.076) were not related to the nutritional status of toddlers. There is a need to increase counseling activities on nutrition awareness to increase community knowledge, especially mothers. So that mothers can pay attention to the nutritional aspects that toddlers will receive to meet their body's needs.